2009
DOI: 10.1002/ijc.24722
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between critical period of estrogen exposure and circulating levels of insulin‐like growth factor‐I (IGF‐I) in breast cancer: evidence from a case‐control study

Abstract: Epidemiological observations suggest that insulin-like growth factor-I (IGF-I), a potent mitogenic and anti-apoptotic peptide, plays a role in the etiology of breast cancer. Estrogen, which is crucial in breast carcinogenesis, both regulates and is influenced by IGF-I family. A case-control study was conducted to assess the role of IGF-I as a biomarker for breast cancer and to evaluate the potential joint effect of circulating IGF-I and critical period of estrogen exposure, as estimated by the interval between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…913 The study comprised subjects attending the Department of Surgery and health examination clinics at the Tri-Service General Hospital Taipei, Taiwan from January 2004 to June 2008. Using hospital chart numbers, 391 women aged 24 to 72 years (the cases) were consecutively selected from subjects with a first confirmed histopathologic diagnosis of breast carcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…913 The study comprised subjects attending the Department of Surgery and health examination clinics at the Tri-Service General Hospital Taipei, Taiwan from January 2004 to June 2008. Using hospital chart numbers, 391 women aged 24 to 72 years (the cases) were consecutively selected from subjects with a first confirmed histopathologic diagnosis of breast carcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…This study is an extension of a case-control study that we have reported on previously [9,13,27]. The study base consisted of subjects attending the Department of Surgery and health examination clinics at the Tri-Service General Hospital Taipei, Taiwan from January 2004 to June 2008.…”
Section: Subjectsmentioning
confidence: 99%
“…This study is an extension of a case-control study that we have reported on previously [19,20]. The study base consisted of subjects attending the Department of Surgery and health examination clinics at the Tri-Service General Hospital Taipei, Taiwan, from January 2004 to November 2006.…”
Section: Study Subjectsmentioning
confidence: 99%